The Role of Participatory Planning in Community-Based Flood and Landslide Disaster Preparedness (Manado City) - Heydi Mayla Silvia Tumembow; Dian Ferriswara; Eny Haryati; Sri Kamariyah (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
Manado City is an area that is vulnerable to floods and landslides, but until now the effectiveness of disaster management still faces serious challenges due to low community involvement in mitigation planning. This study aims to analyze the role of participatory planning in improving community-based disaster preparedness, with a focus on how the Manado City Regional Disaster Management Agency (BPBD: Badan Penanggulangan Bencana Daerah) involves the community in the process of formulating disaster strategies. Using a non-empirical qualitative approach through a literature study method, data were obtained from scientific journals, policy documents, and institutional reports that were analyzed thematically and contextually with reference to the framework of community participation and disaster risk management. The results of the study show that community involvement is still at a symbolic level, limited to the implementation stage, and has not touched the strategic planning process in a meaningful way. Lack of institutional capacity, low disaster literacy, and absence of formal participatory mechanisms are the main inhibiting factors. As a result, disaster programs are often not aligned with local needs and have an impact on low preparedness effectiveness. This study concludes that strengthening community participation in disaster planning is needed to build a more adaptive and iterative preparedness system. Theoretically, the study broadens the understanding of the relevance of participatory planning approaches in community-based disaster management, while practically, the findings provide recommendations for BPBDs and local governments to develop more collaborative and local needs-based policies as a step towards sustainable disaster resilience.